PENENTUAN OPERATOR KARTU SELULER TERBAIK MENGGUNAKAN METODE AHP(ANALITYCAL HIERARCHY PROCESS) - Rizaldi Rizaldi ((JurTI) Jurnal Teknologi Informasi, 2017)
Abstract - The role of telecommunications technology is very important, especially in changing people's lives. The development of technology in the field of communication and information can now be enjoyed by various layers of society, starting from the upper layer, middle layer or lower layer even though the results are not satisfactory. The research entitled "Decision Support System Determination of the best cellular card operator using the AHP method" aims to provide convenience for consumers who want to buy cellular cards from various telecommunications operators according to their needs and save on bags. (economical). The number of cellular card operators provided by telecommunications makes it difficult for consumers to make the right choice, according to the desired criteria. Determining cellular cards with the AHP method is the right method to overcome the problem of determining the best cellular card with many criteria offered by each operator. These criteria include the purchase price of cellular cards, rates, promos and active periods. Keywords - Cellular card operator, Decision support system, Analitycal Hierarchy Process.